The Effect of Group Investigation Method on Mahārah Qirāah of Grade VII Students of Madrasah Tsanawiyah al-Huda Gorontalo City - Bonde, Siti Nur Holisa; Muhammad Nur Iman; Sarif, Suharia (Al-Kalim : Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2023)
This study aims to determine the effect of group investigation method on maharah qiraah of seventh grade students of Madrasah Tsanawiyah Al Huda Gorontalo City. This research is a quantitative study that uses experimental research design with the type of research Quasi Experimental Design. The sample in this study was 7th grade students of Madrasah Tsanawiyah Al Huda Gorontalo City which amounted to 42 students from a population of 196 students with the type of sampling using a sampling technique, namely Purposive Sample. The result obtained from the t-test of pre-test and post-test data is that the hypothesis is accepted. Based on the results of calculations using SPSS 25, it is known that Asymp. Sig. (2-tailed) is 0.003 <0.05, it can be concluded that Ha is accepted and Ho is rejected. So, there is an effect of Group Investigation Method on Maharah Qiraah of Grade 7 Students of Madrasah Tsanawiyah Al Huda Gorontalo City. There is a difference between the results of experimental group students who use group investigation method and control group students who use conventional learning.